RELATIONSHIP OF BLOOD GLUCOSE LEVELS WITH BLOOD PRESSURE IN PEOPLE WITH TYPE 2 DIABETES MELLITUS AT RSU FL TOBING SIBOLGA IN 2021 - Crishartanto Simanungkalit; Meiyati Simatupang; Sridina Sridina (Institute of Computer Science (IOCS), 2022)
Diabetes mellitus is a metabolic disorder caused by abnormalities in insulin secretion, insulin action or both. The IDF recorded 10,700,000 dm sufferers in 2019. Most people with type 2 DM have hypertension. Uncontrolled blood glucose levels can affect blood pressure. This study aims to determine the relationship between blood glucose levels and blood pressure in people with type 2 diabetes mellitus in RSU FL. Tobing Sibolga City. This type of research is analytical observational with a retrospective crosssectional research design. The study used data on fasting blood glucose levels and blood pressure obtained from medical records. The study sample was 632 visits of outpatient type 2 DM patients at FL Hospital. Tobing Sibolga City. The data obtained were tested for normality with Kolmogorov-Smirnov, then tested for correlation using Spearman.